2017
DOI: 10.1002/jat.3454
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional alterations in Malpighian tubules as biomarkers of environmental pollution: synopsis and prospective

Abstract: Although a number of biomarkers of pollutant exposure have been identified in invertebrate species, little is known about the effect on Malpighian tubules playing an essential role in excretion and osmoregulation. Analyses of structural and functional alterations on this organ can be useful to predict the effects at the organism and population level in monitoring studies of environmental pollution. The aim of the present review is to provide a synthesis of existing knowledge on cellular damages induced by xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The morphology of ephemerid MTs is complex and the ultrastructure of ephemerid MT cells is consistent with an ionoregulatory function (Nicholls, 1983;Gaino and Rebora, 2000a,b;Giglio and Brandmayr, 2017). In turn, this is consistent with the role of MTs as an ionoregulatory organ of insects (Pannabecker, 1995;Donini et al, 2008;Jonusaite et al, 2017).…”
Section: Fw Mayfly Nymph Hemolymph Ion Compositionsupporting
confidence: 64%
“…The morphology of ephemerid MTs is complex and the ultrastructure of ephemerid MT cells is consistent with an ionoregulatory function (Nicholls, 1983;Gaino and Rebora, 2000a,b;Giglio and Brandmayr, 2017). In turn, this is consistent with the role of MTs as an ionoregulatory organ of insects (Pannabecker, 1995;Donini et al, 2008;Jonusaite et al, 2017).…”
Section: Fw Mayfly Nymph Hemolymph Ion Compositionsupporting
confidence: 64%
“…According to the severity scores of the histopathological changes, dose-dependent effects were observed only in LP plant type, which caused malpighian pyknosis ( Table 6). Malpighian tubules are the primary organ in insects used for excretion and osmoregulation [48]. The condensation of chromatin and nucleus in malpighian pyknotic cells may result from apoptosis; programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium of the intestinal tract is the first barrier against assimilation of toxicants into the organism but metals readily cross the gut epithelium into the hemolymph and are then transported into other tissues (Leonard et al 2009). A few studies highlight the fact that exposure to environmental contaminants via contaminated food may cause sublethal effects on the Malpighian tubules (Giglio and Brandmayr 2017). However, the ultrastructural analysis of the Malpighian tubules of the ground beetle Carabus lefebvrei exposed to soil contaminated with different metals showed that potentially toxic metals are safely stored in intracellular compartments in an insoluble and physiologically inactive form (Talarico et al 2014).…”
Section: Resultsmentioning
confidence: 99%